Celebrating Homer's landscapes : Troy and Ithaca revisited - Luce, John Victor, 1920- (Yale University Press, 1998)
In this beautiful and engaging book, an eminent authority on Homeric texts takes us on a tour of the main localities that Homer paints so vividly in his Iliad and Odyssey. Providing numerous photographs of the terrain and "ing liberally from the two epics, J. V. Luce argues convincingly that Homer's descriptions of the ancient landscape, far from being poetic fantasies, are accurate in every detail.Luce surveys what Homer tells us about the environs of Troy and Ithaca, applying the developing science of narratology to the Homeric depiction of landscape. He also incorporates information about Troy that has been obtained in the past two decades, in particular new geophysical information about the comparatively recent alluviation of the Trojan plain and new archaeological data about Troy that reveals that the fortified area of the city was ten times as large as previously supposed. Tracing the ebb and flow of battle as described in the Iliad, Luce shows how Homer`s account is consistent with this new picture of the plain. He also demonstrates that the topography of Ithaca is sketched with such accuracy that Homer must have had firsthand knowledge of the terrain. Luce`s book is a significant contribution for specialists and a delightful companion for readers of Homer or visitors to the ancient sites.